Peningkatan Kualitas Permukiman Suku Bajo Desa Popisi Kecamatan Bangggai Utara Kabupaten Banggai Laut: (Studi Penanganan Permukiman Masyarakat Suku Bajo) - Ayu Afrianti; Batara Surya; Kamran Aksa (Journal of Urban Planning Studies, 2021)
Abstract. The purpose of this study was to determine the influence factor of the environmental quality of settlements of the Bajo ethnic community in Popisi Village, North Banggai District, Banggai Laut Regency and to determine the strategy for improving the quality of settlements for the Bajo ethnic community of Popisi Village, North Banggai District, Banggai Laut Regency. This study uses quantitative research with a quantitative approach, then the sample selection method in this study is Simple Random Sampling. The analysis used in this study is to use multiple regression analysis and SWOT analysis. The main conclusion of this research is that the influence factor of the environmental quality of the Popisi Village community settlements is influenced, namely the accessibility factor, population growth, natural and cultural factors of the Popisi Village community, while to improve the quality of the residential environment, an SO strategy is needed, namely using opportunities to maintain strength.